Vibration reduction on circular saw blades with vibroacoustic metamaterials - Rieß, Sebastian; Kaal, William; Herold, Sven (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
The presented work focuses on the experimental investigation of a vibroacoustic metamaterial integrated into a spinning circular saw blade. Vibroacoustic metamaterials are a novel technology for broadband vibration reduction. Built from an array of local resonators, a broadband vibration reduction characteristic in the frequency domain (a so-called stop band) can be achieved. A design of a vibroacoustic metamaterial suitable for integration into a circular saw blade is developed and a numerical stop band prediction is performed. The resonators of the vibroacoustic metamaterial are integrated into the saw blade with a water jet cutting machine to create slots, forming flaps that are free to oscillate. The structural dynamic behavior of the saw blade with integrated vibroacoustic metamaterial is experimentally investigated on a rotor dynamic test bench and compared to that of a standard saw blade. The saw blades are excited by an automatic impulse hammer and the resulting out-of-plane vibrations are measured with a laser vibrometer at two different radii. Measurements are conducted at different rotational speeds up to 1800 rpm. Up to rotational speeds of 1000 rpm a stop band characteristic in the frequency range of 1900–2500 Hz is observed.